1990
DOI: 10.1007/bf02540504
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the γ‐linolenic acid content by solvent winterization of fungal oil extracted fromMortierella genus

Abstract: The fungal oil extracted from Mortierella ramanniana var. angulispora (IFO 8187) was solvent winterized in order to raise the content of 7-1inolenic acid (GLA). Effects of winterization conditions (solvent, oil concentration in the solvent and temperature) and changes of glyceride compositions were discussed. The fungal oil was separated into four diglycerides and 17 triglycerides (TG) with high performance liquid chromatography. The predominant species were POO, POP and LOP, whose contents were 24.4, 22.9 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 16 publications
3
30
1
Order By: Relevance
“…Chemical methods reported for enriching GLA include solvent winterization [18], urea fractionation [19], a combination of urea fractionation and silica gel chromatography [20], and the use of Y-Zeolite to concentrate GLA ethyl esters [21]. Using a low-temperature solvent crystallization process followed by lipase-catalyzed esterification, Ju and Jen [22] obtained very pure GLA from BO fatty acids.…”
Section: Extraction Of Glamentioning
confidence: 99%
“…Chemical methods reported for enriching GLA include solvent winterization [18], urea fractionation [19], a combination of urea fractionation and silica gel chromatography [20], and the use of Y-Zeolite to concentrate GLA ethyl esters [21]. Using a low-temperature solvent crystallization process followed by lipase-catalyzed esterification, Ju and Jen [22] obtained very pure GLA from BO fatty acids.…”
Section: Extraction Of Glamentioning
confidence: 99%
“…After crystallization is complete, the solid phase is separated from the liquid phase by one of several physical processes (4,5). Alternatively, solvent (typically acetone) crystallization is used for promoting TAG crystal formation, because TAG at low temperature generally form more stable crystals with solvent than without solvent (6). Accordingly, TAG species with a higher (or lower) level of desirable (or undesirable) fatty acids can be separated by both fractional crystallization processes for use in nutritional or functional food applications.…”
mentioning
confidence: 99%
“…Crystallization of SFA from a solution of fatty acid mixture in organic solvents, especially a polar type, is a promising way of separation. It has been reported that use of different organic solvents and temperatures affects the concentration of PUFA [22]. With proper choice of solvent and temperature, PUFA can be concentrated into a non-crystallized fraction.…”
Section: Low-temperature Crystallization Methodsmentioning
confidence: 99%